2021
DOI: 10.1038/s41598-021-99724-9
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis of the prognostic and immunological role of PSMB8

Abstract: Recently some evidence has demonstrated the significance of PSMB8 in various malignancies. Nevertheless, PSMB8 (proteasome subunit beta 8), more familiar in the field of immunology contributing to the process of antigen presentation, is indeterminate in the role as a survival predictor of human pan-cancer. Besides, how PSMB8 interacts with immune cell infiltration in the tumor microenvironment requires further research. We then penetrated into the analysis of the PSMB8 expression profile among 33 types of canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…: PSMB8, NFKB1, ALB, EDN1 , and ESR1 . Proteasome subunit beta 8) is a catalytic subunit involved in tumor infiltration and neuroinflammation ( 21 , 22 ). Nuclear factor kappa B1 is a classic transcriptional regulator with multi-system involvement ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…: PSMB8, NFKB1, ALB, EDN1 , and ESR1 . Proteasome subunit beta 8) is a catalytic subunit involved in tumor infiltration and neuroinflammation ( 21 , 22 ). Nuclear factor kappa B1 is a classic transcriptional regulator with multi-system involvement ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the member of immunoproteasome, LMP7 participated in the antigen presentation, cell cycle regulation, and cell signal transduction (18)(19)(20). At present, many studies show that abnormal expression of PSMB8 correlates with multiple cancers, including BC (21)(22)(23)(24)(25). However, the results obtained from different studies are not the same.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular subtype of breast cancer was determined after assessing the receptor status [expression of ER and PR], HER-2 status and proliferative activity (Ki67 expression) in biopsy and surgical specimens using the According to the American Society of Clinical Oncology/ College of American Pathologists (ASCO/CAP) guidelines, ER and PR expression was considered positive when nuclear immunoreactivity was ≥1% of tumor cells (42). HER-2positive protein status was defined as a score of 3+ or 2+ by IHC along with confirmed amplification of the c-erbB2 gene using fluorescence in situ hybridization (FISH).…”
Section: Ihcmentioning
confidence: 99%
“…Using various databases and platforms (Oncomine, cBioPortal and Cytoscaped and METABRIC, TCGA, CCLE Project and STRING), numerous published studies demonstrated the prognostic value of the gene expressions of various proteasome subunits both in breast cancer and in other cancers in terms of long-term overall and longterm progression-free survivals. In particular, the authors reported on the prognostic significance of the expression of the PSMC family genes encoding subunits of the 19S regulatory complex of the proteasomes, the expression of the PSMA family genes encoding the α subunits of the proteasome nucleus, and the expression of the PSMB8 gene responsible for the formation of the immune LMP7 subunit (40)(41)(42). Almost all databases concern the expression of genes encoding various subunits of the proteasome complex.…”
Section: Introductionmentioning
confidence: 99%